2013
DOI: 10.1123/jsr.22.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Superficial Heat to the Knee on Quadriceps Function in Individuals With Quadriceps Inhibition

Abstract: Superficial heat to the knee joint using a cervical moist-heat pack did not influence quadriceps function in individuals with AMI in the quadriceps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(38 reference statements)
0
8
0
2
Order By: Relevance
“…Another study found application of local anaesthetic cream had no effect in improving the sensorimotor function of the knee in subjects with ACL injury 33. An RCT of 12 patients with a history of knee-joint pathology and quadriceps CAR of <90% evaluated superficial heat application and found no effect on quadriceps function 34…”
Section: Resultsmentioning
confidence: 99%
“…Another study found application of local anaesthetic cream had no effect in improving the sensorimotor function of the knee in subjects with ACL injury 33. An RCT of 12 patients with a history of knee-joint pathology and quadriceps CAR of <90% evaluated superficial heat application and found no effect on quadriceps function 34…”
Section: Resultsmentioning
confidence: 99%
“…Mi- crocurrent conductance, serum myoglobin, and muscular strength have shown changes as a result of tissue injury [6] [10] [18]. However, these outcome measures have not been tested concurrently so their result could be compared.…”
Section: Discussionmentioning
confidence: 99%
“…When testing subjects with arthrogenic inhibition for muscles around the knee, a moist heat pack did not create any significant changes in the strength of knee extension [18]. However, another study showed strength increases at the knee after heat for subjects with osteoarthritis [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although often used as a heating agent, the application of superficial heat has not yielded success as a disinhibitory modality, 19 making the nonthermal mechanical properties a particular interest. Nonthermal ultrasound is reported to influence osseous and cutaneous receptors important in fracture 20,21 and wound healing 22 using pulsed energy; however, the influence on articular mechanoreceptors is unknown.…”
mentioning
confidence: 99%